Persepsi mahasiswa terhadap program Green Campus dalam mewujudkan perguruan tinggi yang berkelanjutan (studi kasus: Universitas Negeri Malang) - Rachmadian, Robby Hilmi; Sumarmi, Sumarmi; Masruroh, Heni; Utaya, Sugeng; Suharto, Yusuf (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Universities as educational institutions are obliged to provide understanding and attitudes to students. State University of Malang (UM) as a university that implements the green campus program has made various efforts such as green building for waste management, water and transportation. Therefore, the aim of this research is to determine student perceptions of the green campus program in realizing sustainable university. This research was conducted using descriptive quantitative methods. Data collection techniques use field surveys and questionnaires. Proportionate stratified random sampling was used to determine the sample. Data analysis techniques use validity and reliability tests to measure the validity of the instrument. The research respondents were 92 UM students from 9 faculties. UM students have a relatively high understanding of the green campus program as evidenced by 73.9% of students being committed to supporting a sustainable university environment. Apart from that, UM students think that maintaining environmental sustainability can have an impact on the quality of learning and increase positive feelings in the campus area. However, in order to maintain a sustainable university environment and increase student understanding at UM, it is necessary to carry out a separate study and establish regulations governing environmental sustainability involving the entire academic community.